Video Media for Learning Cultural Diversity in the Surrounding Environment Based on Local Wisdom of the Ngerebong Tradition for Grade IV Elementary Schools - Mardaragawan, I Made Leo; Agung , Anak Agung Gede (Universitas Pendidikan Ganesha, 2024)
The use of lecture methods and learning media that are not yet effective has an impact on learning objectives that have not been achieved optimally. This research aims to develop the video media for learning cultural diversity in the surrounding environment based on the local wisdom of the Ngerebong tradition for grade IV elementary schools. This type of research is a development using the ADDIE model. The data collection method uses ordinary multiple choice objective tests as well as questionnaires and quantitative descriptive data analysis techniques and inferential statistics. The results of the research are the design of learning video media with the results of design assessments from design experts with a percentage of 90.90% who are in Very Good qualifications. The quality of the learning videos shows that the results of the lesson content expert test were 100%, the instructional design expert test was 90.62%, the learning media expert test was 91.66%, the individual trial was 93.33% and the small group trial was 92%. 77%. The effectiveness of learning videos based on the results of the t-test obtained a tcount of -28.33. Then the tcount price is compared with the ttable price with db 29. The ttable price for db 29 with a significance level of 5% (α = 0.05) is 1.699. This means that the tcount is greater than the ttable, so H0 is rejected and H1 is accepted. Thus, it can be concluded that the learning video media based on the local wisdom of the ngerebong tradition is effectively used in cultural diversity material in the environment surrounding the content of Pancasila education in grade IV elementary schools.